Agro-physiologic effects of compost and biochar produced at different temperatures on growth, photosynthetic pigment and micronutrients uptake of maize crop (2016)
The production and use of biochart and compost present many opportunities for soil improvement and agricultural productivity. However, the yield and performance of biochar depend on the feedstocks, pyrolysing temperatures and rate of application. Experiments were conducted to find out the effect of compost and biochar produced from two different feed stocks (Rice husk and Mexican sunflower) and pyrolysed at different temperatures (300, 350 and 400°C) on the growth, yield, nutrient uptake and chlorophyll contents of maize (Zea mays L.,). These were applied at three levels (5, 10 and 15 ton/ha) and the pots were laid out in a Completely Randomized Design (CRD) with four replicates. Data were collected on growth and yield attributes of maize, photosynthetic pigments and nutrient uptake by maize crop.The results showed that the feedstock pyrolyzed at temperature between 300 to 350°C and compost applied at higher rate between 10 to 15 ton/ha performed better. On the growth and yield parameters, compost and biochar at relatively low temperature and applied at 15 t/ha performed better than other treatments including control both at the main and residual experiments On the residual effect, the two types of biochar performed better than compost most especially sunflower biochar pyrolysed at 300 and 350°C and applied at 15 t/ha. The chlorophyll formation was enhanced more in maize treated with higher rates of biochar than lower rates. The result indicates that depending on feedstock, biochar and compost have potentials to serve as nutrient sources.